Effects of extracts from Tiam seeds on diamondback moth (Plutella xylostella Linn.) - Phadoongsombat, N.; Butpha, T.; Pipithsangchan, S.; Subhadhirasakul, S. (Songklanakarin Journal of Science and Technology (SJST), 2004)
n-Hexane and methanolic extracts from the seeds of Azadirachta excelsa Jack. (Tiam) and A. indica var. siamensis Valeton, Bacillus thuringiensis var. kurstaki HD-1 and abamectin were tested for mortality effect on the 2nd and the 3rd instar larvae of diamondback moth (Plutella xylostella Linn.) by topical application and feeding methods. Among the seed extracts, the methanolic extract from A. excelsa was the most active. Its LC50 at 72 hours after testing on the 2nd and the 3rd instar larvae of diamondback moth using topical application was 16,298.4 mg/l and 28,225.4 mg/l, respectively, and that by feeding method was 3,921.1 mg/l and 5,136.2 mg/l, respectively. The methanolic extract was more active than the n-hexane extract in each plant. Among the tested samples, abamectin, a chemical insecticide, showed the highest insecticidal effect. Its LC50 at 72 hours after testing on the 2nd and the 3rd instar larvae of diamondback moth using topical application was 81.3 mg/l and 227.9 mg/l, respectively, and that by feeding was 44.2 mg/l and 112.8 mg/l, respectively. The methanolic extract of A. excelsa to reduce the population of the 2nd instar larvae of diamondback moth on Chinese kale (Brassica alboglabra Bailey) was not significantly different from that of the methanolic extract of A. indica var. siamensis. The n-hexane extract at the concentration of 5% of A. excelsa to show antioviposition effect of the diamondback moth on Chinese kale was more active than the n-hexane extract of A. indica var. siamensis.